Fast and efficient separation of cytokinins from auxin and abscisic acid and their purification using mixed-mode solid-phase extraction - Dobrev, Petre Ivanov; Kamínek, Miroslav (Journal of chromatography. A, 2002)
A method for separation of cytokinins from auxin and abscisic acid, which allows further separation of cytokinin ribotides from cytokinin bases, ribosides and glucosides and their purification on a single Oasis MCX column was developed. Due to the mixed reversed-phase and cation-exchange mode of the Oasis MCX sorbent the cationic cytokinin bases, ribosides and glucosides as well as the anionic auxin, abscisic acid and cytokinin ribotides are retained and can be sequentially eluted by solvents containing different concentrations of methanol and ammonium hydroxide. Characteristics of the method are high recoveries of analyzed phytohormones and their sufficient purity for quantification by HPLC-ELISA (RIA) or HPLC-MS.
Keywords: Abscisic Acid; hmotnostní spektrometrie; Chromatography, High Pressure Liquid; kyseliny indoloctové; Mass Spectrometry; Indoleacetic Acids; Cytokinins; ELISA; cytokininy; Enzyme-Linked Immunosorbent Assay; vysokoúčinná kapalinová chromatografie; kyselina abscisová